Mechanical Pulp from Eucalyptus ('M.H' Mysore origin) - Guha, S. R. D.; Madan, R. N. (Indian Forester, 1964)
Laboratory experiments on the production of mechanical pulp from Eucalyptus (M.H.) are described. Standard pulp sheets were made from this species and 40 per cent imported bleached sulphate wood pulp. Strength properties of standard sheets prepared from mechanical pulp produced under suitable conditions are satisfactory for the production of newsprint, but the colour is poor. Pulp of satisfactory colour for newsprint, can be obtained by bleaching with 10 per cent available chlorine.